Dilema Pertanggungjawaban Pidana Pejabat Negara dalam Negara Hukum Demokratis - Kholik, Muhamad Abdul; Zulfaidah, Rena; Septiani, Ernida (Interdisciplinary Explorations in Research Journal, 2025)
This article aims to analyze the dilemma of criminal liability of public officials within the framework of a democratic rule of law, particularly concerning the phenomenon of criminalization of public policies in Indonesia. The main issues examined include the conceptual boundaries between policy errors and criminal acts, the problems in applying criminal law to public policies, and the formulation of an ideal and just model of criminal liability for public officials. This research employs a normative juridical method with conceptual, statutory, and case approaches by analyzing the New Indonesian Criminal Code, relevant regulations, and legal doctrines in criminal and administrative law. The results show that criminal prosecution of public officials is often conducted without clear parameters, leading to fear in decision-making and hindering bureaucratic innovation. It is found that state financial loss alone cannot automatically serve as a basis for criminal liability without proof of fault, abuse of authority, and malicious intent. The study emphasizes the importance of separating legal regimes between administrative, civil, and criminal law by placing criminal law as ultimum remedium. The ideal model proposed is a criminal liability system based on constitutional parameters that require proof of mens rea, intentional abuse of authority, and personal benefit. The study concludes that law enforcement against public officials must be carried out proportionally and fairly to prevent the criminalization of policies while still ensuring accountability for officials who genuinely commit criminal acts.